Docetaxel and cyclophosphamide as adjuvant chemotherapy for early breast cancer: primary prophylaxis with G-CSF is required. (September 2013) - Lakhanpal, Roopa; Stuart-Harris, Robin; Chan, Arlene; Kotasek, Dusan; Beith, Jane; Cuff, Katharine; Bastick, Patricia; Lee, Clara
SUMMARY Aim: To determine the incidence of febrile neutropenia (FN) associated with the use of docetaxel and cyclophosphamide (TC) as adjuvant chemotherapy for early breast cancer (EBC) and also the grade of neutropenia after cycle 1 of TC.Methods: We conducted a multicenter retrospective audit of women with EBC treated with TC between January 2010 and July 2011, recruited from seven Australian centers.Results: Of a total of 368 previously untreated women with EBC who received TC, 300 were evaluable for FN and 304 were evaluable for neutropenia after cycle 1 of TC. Overall, 73 (24.3%) patients developed FN. The incidence of FN was highest after cycle 1 of TC and was significantly higher in women under 65 years of age (p = 0.007). There was significant variation in the incidence of FN between participating sites (p < 0.001). Eight patients (2.6%) developed grade 3 neutropenia and 191 patients (62.8%) developed grade 4 neutropenia.Conclusion: TC as adjuvant chemotherapy for EBC is associated with a 24.3% incidence of FN and a 65.4% incidence of grade 3 or 4 neutropenia. The high incidence of FN and severe neutropenia warrant the use of G-CSF as primary prophylaxis.